Hookah Smoking in Incidence with Asymptomatic Gout - Israa A. Mohammed Jumaah Jumaah; Shatha A. Demerchi; Abdulrahman Ahmed Mahmood (Jurnal Kesehatan Masyarakat, 2025)
Water pipe smoking (WPS) has become very popular worldwide, especially among young people. Its widespread use makes it a risk factor for various diseases. In this study, we hypothesized that water pipe smoking is a cause of asymptomatic gout and prostate cancer and affects salivary pH and serum magnesium (Mg) levels. The study was conducted with 80 participants (60 in the hookah smoking group and 20 in the control group) in Kirkuk, Iraq. Serum uric acid, magnesium (Mg), prostate-specific antigen (PSA), and saliva pH were tested and analyzed for both groups. The result was a significant increase in serum uric acid concentration without any notable changes in saliva pH, serum PSA, and serum magnesium levels. Also, based on tabular data using the Pearson correlation coefficient, a significant positive correlation between waterpipe smoking and serum uric acid levels was examined, but a significant negative correlation between serum PSA and serum Mg levels was assessed. Finally, we also observed small changes in serum uric acid, serum PSA, and serum magnesium levels over extended period (less than 5 years or ≥ 5 years) among waterpipe smokers.